Modulating Antimicrobial Activity and Mammalian Cell Biocompatibility with Glucosamine-Functionalized Star Polymers - Wong, Edgar H. H. (2016)
The development of novel reagents and antibiotics for combating multidrug resistance bacteria has received significant attention in recent years. In this study, new antimicrobial star polymers (14–26 nm in diameter) that consist of mixtures of polylysine and glycopolymer arms were developed and were shown to possess antimicrobial efficacy toward Gram positive bacteria including methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE) (with MIC values as low as 16 μg mL–1) while being non-hemolytic (HC50 > 10 000 μg mL–1) and exhibit excellent mammalian cell biocompatibility. Structure function analysis indicated that the antimicrobial activity and mammalian cell biocompatibility of the star nanoparticles could be optimized by modifying the molar ratio of polylysine to glycopolymers arms. The technology described herein thus represents an innovative approach that could be used to fight deadly infectious diseases.